2016
DOI: 10.1159/000445697
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IgA Class Switch Recombination in Immunoglobulin A Nephropathy: Retinoic Acid Signaling and BATF

Abstract: Background: Immunoglobulin (Ig) A nephropathy (IgAN) is the finding of immune deposits predominantly containing polymeric IgA in the glomerular mesangium on renal biopsy. Increasing evidence suggested that retinoic acid (RA) signaling selectively induces IgA isotype switching and basic leucine zipper transcription factor, ATF-like (BATF) controls the global regulators of class switch recombination (CSR) in lymphocytes. Great effort has been paid to identify whether impaired immune regulation along the ‘mucosa-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…As a nuclear retinoic acid receptor, RARa plays multiple roles in biological processes, including organogenesis (Mendelsohn et al, 1999), homeostasis (Canete et al, 2017), and tumor metastasis (Doi et al, 2015). Furthermore, RARa is connected with kidney diseases, such as HIVassociated nephropathy (Ratnam et al, 2011), Ig A nephropathy (He et al, 2016), and crescentic glomerulonephritis (Dai et al, 2017). Most recently, RARa has been suggested to mediate ECM deposition in the progression of RIF in vitro and in vivo (Long et al, 2012;Chen et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a nuclear retinoic acid receptor, RARa plays multiple roles in biological processes, including organogenesis (Mendelsohn et al, 1999), homeostasis (Canete et al, 2017), and tumor metastasis (Doi et al, 2015). Furthermore, RARa is connected with kidney diseases, such as HIVassociated nephropathy (Ratnam et al, 2011), Ig A nephropathy (He et al, 2016), and crescentic glomerulonephritis (Dai et al, 2017). Most recently, RARa has been suggested to mediate ECM deposition in the progression of RIF in vitro and in vivo (Long et al, 2012;Chen et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies conducted by He et al () and Ratnam et al () suggested that activation of RARα protected against the development of HIV‐associated nephropathy. He et al () later found that RARα was involved in the immunoglobulin class switch recombination of IgA nephropathy. In addition, our previous studies have shown that RARα exerts anti‐fibrotic effects on tubulointerstitial fibrosis, because it is associated with matrix deposition and degradation in fibrotic kidneys (Long et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue samples were prepared as previously described [27,28,29]. Renal cortex tissue was lysed in RIPA Lysis Buffer (Beyotime Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoglobulin A (IgA) nephropathy (IgAN) is a kind of immune complex nephritis in which IgA deposits in the mesangial area of the glomerulus (1)(2)(3). IgAN is the most prevalent primary glomerular disease worldwide and in China, IgAN patients account for about 45% of primary glomerular disease (4)(5)(6)(7). Studies have shown that renal fibrosis is an important factor affecting the progression and prognosis of IgAN (8,9).…”
Section: Introductionmentioning
confidence: 99%